To Estimation of Efficient Usage of Organic Fuel in the Cycle of Steam Power Installations - A. P. Nesenchuk; A. V. Begljak; T. V. Rizova; D. I. Shklovchik; M. A. Yarmolnik; L. I. Kachar (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2013)
Tendencies of power engineering development in the world were shown in this article. There were carried out the thermodynamic Analysis of efficient usage of different types of fuel. This article shows the obtained result, which reflects that low-calorie fuel (from the point of thermodynamics) is more efficient to use at steam power stations then high-energy fuel.